Analisis Kelengkapan Pengisian dan Ketepatan Waktu Pengembalian Dokumen Rekam Medis Rawat Inap Rumah Sakit Ibu dan Anak Zainab Pekanbaru Tahun 2025 - Hashifah Faizah; Doni Jepisah; Abdurrachman Rafiqi Abdi (LPPM Institut Pendidikan Nusantara Global, 2026)
Inpatient medical records are essential documents that function as clinical, administrative, legal, financial, research, and managerial information sources in hospital health services. The completeness of documentation and the timeliness of returning medical record files are important indicators of service quality, continuity of care, and patient safety. Incomplete records and delayed returns may affect clinical decision-making, reporting accuracy, and hospital performance evaluation. This study aims to analyze the completeness of documentation and the timeliness of returning inpatient medical records at Zainab Mother and Child Hospital, Pekanbaru, in 2025, as well as to identify factors influencing these processes. This study employed a qualitative approach using a case study design. Data were collected through direct observation of inpatient medical record workflows, in-depth interviews with medical record officers, nurses, and physicians, and document review of standard operating procedures and medical record timeliness reports. Data triangulation was applied to ensure the credibility of the findings. The results indicate that incomplete documentation was still found in several important components, particularly in patient progress notes and authentication sections. In addition, delays in returning medical record files beyond the established 2 × 24-hour standard were identified. Contributing factors included limited human resources, high workload, lack of routine monitoring and evaluation, and inadequate supporting facilities. This study concludes that improving the quality of inpatient medical record management requires strengthening human resource competencies, enforcing compliance with standard operating procedures, and enhancing supervision and coordination among related service units.